Sistem Pakar Untuk Mendeteksi Kerusakan AC Menerapkan Metode Graf or Algorithm - Vera, Eni (TIN: Terapan Informatika Nusantara, 2020)
The development of electric technology is currently running very fast. One of the rapidly growing electronics is smart Electric. important part of this smart electronic development is AC. This electronic device is very vulnerable to damage to devices or systems that are rarely known by many people and experience difficulties. detecting AC damage, an algorithm method is needed to learn from damage to existing item items. The Graph Or Algorithm method is a method that can solve the problem of detecting the AC damage